Types and Abundance of Phytoplankton in The Sepinang Lake, Siak Hulu Sub-District, Kampar District, Riau Province - Yunita, Sarah Amelia; Siagian, Madju; Simarmata, Asmika Harnalin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThere were several human activities around the Sepinang Lake such as agriculture and palm plantation contributes the input of organic and anorganic matter that influence the type and abundance of phytoplankton. To understand the types and abundances of phytoplankton present in the Sepinang Lake, a researchhas been conducted in March-April 2018. There were three sampling points, namely in the inlet, in the middle of the lake, and in the end of the lake. In each sampling point,water was sampled from the surface and 2 Secchi depth. Samplings were conducted 3 times, once/week.Water quality parameters measured were temperature, transparency, depth, dissolved oxygen, CO2, nitrate, phosphate and pH.Results shown that there were 47 species of phytoplankton that were belonged to 5 divisions, namely Chrysophyta (10 species), Chlorophyta (25 species), Cyanophyta (8 species), Euglenophyta (3 species) and Cryptophyta (1 species). The phytoplankton abundance of the Sepinang Lake was 106,490 â€“ 150,650 cells/L. The most common type of phytoplankton present wasMonoraphodium griffithii.Result shown that the temperature was 30.6-320C, transparency was 49.3-62.8 cm, depth was 211-223.6 cm, dissolved oxygen was 4.22-5.58 mg/L, CO2 was 11.32-13.32 mg/L, nitrate was 0.07-0.23 mg/L, phosphate was 0.09-0.23 mg/L and pH was 5.3-5.6. Based on the type and abundance of phytoplankton present, it can be concluded that the Sepinang Lake can be categorized as mesotrophic.Â Keywords: Kampar River, Oxbow Lake, Mesotrophic, Monoraphodium